Integrative physiology of human adipose tissue. - Frayn, K; Karpe, F; Fielding, B; Macdonald, I; Coppack, S (2003)
Adipose tissue is now recognised as a highly active metabolic and endocrine organ. Great strides have been made in uncovering the multiple functions of the adipocyte in cellular and molecular detail, but it is essential to remember that adipose tissue normally operates as a structured whole. Its functions are regulated by multiple external influences such as autonomic nervous system activity, the rate of blood flow and the delivery of a complex mix of substrates and hormones in the plasma. Attempting to understand how all these factors converge and regulate adipose tissue function is a prime example of integrative physiology. Adipose tissue metabolism is extremely dynamic, and the supply of and removal of substrates in the blood is acutely regulated according to the nutritional state. Adipose tissue possesses the ability to a very large extent to modulate its own metabolic activities, including differentiation of new adipocytes and production of blood vessels as necessary to accommodate increasing fat stores. At the same time, adipocytes signal to other tissues to regulate their energy metabolism in accordance with the body's nutritional state. Ultimately adipocyte fat stores have to match the body's overall surplus or deficit of energy. This implies the existence of one (or more) signal(s) to the adipose tissue that reflects the body's energy status, and points once again to the need for an integrative view of adipose tissue function.